Optimal Placement of Embedded Generation in Active Distribution System Using Dragonfly Algorithm - et. al., Ram Deshmukh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a method for optimum position and size of Embedded Generation (EG) in the active distribution network using the Dragonfly Algorithm (DA). The reduction of power losses of the active distribution system was considered to be an objective function. Voltage limits and thermal limits of feeders in the radial distribution system have been considered as a limitation of the optimization problem. The proposed approach has been introduced for the PG & E 69 bus radial distribution network. Reduction of the active power losses of the radial distribution system by selecting the correct location and size of the EG units using the proposed method has been achieved in the simulated results of the test system.